Traditional birth attendants lack basic information on HIV and safe delivery practices in rural Mysore, India - Adamson Paul; Kumar Bhavana N; Madhivanan Purnima; Krupp Karl (BMC, 2010)
Abstract Background There is little research on HIV awareness and practices of traditional birth attendants (TBA) in India. This study investigated knowledge and attitudes among rural TBA in Karnataka as part of a project examining how traditional birth attendants could be integrated into prevention-of-mother-to-child transmission of HIV (PMTCT) programs in India. Methods A cross-sectional survey was conducted between March 2008 and January 2009 among TBA in 144 villages in Mysore Taluk, Karnataka. Following informed consent, TBA underwent an interviewer-administered questionnaire in the local language of Kannada on practices and knowledge around birthing and HIV/PMTCT. Results Of the 417 TBA surveyed, the median age was 52 years and 96% were Hindus. A majority (324, 77.7%) had no formal schooling, 88 (21.1%) had up to 7 years and 5 (1%) had more than 7 yrs of education. Only 51 of the 417 TBA (12%) reported hearing about HIV/AIDS. Of those who had heard about HIV/AIDS, only 36 (72%) correctly reported that the virus could be spread from mother to child; 37 (74%) identified unprotected sex as a mode of transmission; and 26 (51%) correctly said healthy looking people could spread HIV. Just 22 (44%) knew that infected mothers could lower the risk of transmitting the virus to their infants. An overwhelming majority of TBA (401, 96.2%) did not provide antenatal care to their clients. Over half (254, 61%) said they would refer the woman to a hospital if she bled before delivery, and only 53 (13%) felt referral was necessary if excessive bleeding occurred after birth. Conclusions Traditional birth attendants will continue to play an important role in maternal child health in India for the foreseeable future. This study demonstrates that a majority of TBA lack basic information about HIV/AIDS and safe delivery practices. Given the ongoing shortage of skilled birth attendance in rural areas, more studies are needed to examine whether TBA should be trained and integrated into PMTCT and maternal child health programs in India.